BRIDGING THE GAP: DOES ISLAMIC EDUCATION ADDRESS FINANCIAL LITERACY NEEDS? - Faizah, Ima; Haris, Abdul (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the integration of Islamic financial literacy within the curriculum documents, syllabi, and textbooks of Islamic Religious Education (PAI) at the Senior High School (SMA) level. The objective is motivated by the low levels of Islamic financial literacy in Indonesia, which highlights the need to incorporate these values into the educational system to address economic challenges in the digital era. Method: The research employs a literature review and content analysis approach to examine official documents, such as the PAI Learning Outcomes (Capaian Pembelajaran) and PAI textbooks under the Kurikulum Merdeka framework. These resources were analyzed to identify the extent of Islamic financial literacy representation. Results: The findings reveal that Islamic financial literacy is reflected in certain themes within PAI textbooks, such as discouraging consumerism and introducing Islamic financial institutions. However, its scope remains limited, particularly in the areas of financial planning, investment, and adaptation to digital financial technologies. Novelty: This study underscores the need for a more comprehensive PAI curriculum by recommending the inclusion of topics on Islamic financial management principles, adaptation to Islamic fintech, and strengthening the values of maqashid sharia in financial management. These additions aim to better equip students with essential financial literacy skills in line with Islamic values.